„Hát én immár kit válasszak?” – Gondolatok a párválasztás bibliai és lélektani alapjairól - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
“Well, whom should I choose” – Thoughts about the biblical and psychological foundations of marriage. The study begins with the enumeration of bible passages which show that the marriage of men and women is something good, it is based on God’s ordinance. The institution of marriage is in a crisis lately, the divorce rate is growing fast, which can be explained with choosing the wrong partner among other reasons. Some decades earlier the parents decided whom should their children marry, which was truly painful sometimes, for example in the Hungarian folklore there are many sad songs and ballads about young people who were obliged to marry someone. But is it easier today in our society? We have total freedom to choose our partner, and it means we have the chance to make a wrong choice. There isn’t a 100% sure method for choosing a partner, but one key of doing it successfully is getting to know the partner well, which needs time, patience and deep conversations. The study presents 5 factors that determine the development of our character: 1- 2. Parents, 3.Friends/Contemporaries 4. Attitude to knowledge 5. Attitude to money, wealth, knowing these is the way to get to know the most about our partner. Last but not least it is as well important to discover the values which are important for the partner, because in a good relationship the common values and interests are necessary.